TCP/IP sockets in C : practical guide for programmers - Makofske, David B. (Morgan Kaufmann practical guides series., 2004)
"TCP/IP sockets in C is an excellent book for anyone interested in writing network applications using Microsoft .Net frameworks. It is a unique combination of well written concise text and rich carefully selected set of working examples. For the beginner of network programming, it's a good starting book; on the other hand professionals could also take advantage of excellent handy sample code snippets and material on topics like message parsing and asynchronous programming." Adarsh Khare, SDT, .Net Frameworks Team, Microsoft Corporation The popularity of the C language and the .NET framework is ever rising due to its ease of use, the extensive class libraries available in the .NET Framework, and the ubiquity of the Microsoft Windows operating system, to name a few advantages. TCP/IP Sockets in C focuses on the Sockets API, the de facto standard for writing network applications in any programming language. Starting with simple client and server programs that use TCP/IP (the Internet protocol suite), students and practitioners quickly learn the basics and move on to firsthand experience with advanced topics including non-blocking sockets, multiplexing, threads, asynchronous programming, and multicasting. Key network programming concepts such as framing, performance and deadlocks are illustrated through hands-on examples. Using a detailed yet clear, concise approach, this book includes numerous code examples and focused discussions to provide a solid understanding of programming TCP/IP sockets in C. Features *Tutorial-based instruction in key sockets programming techniques complemented by numerous code examples throughout *Discussion moves quickly into the C Sockets API definition and code examples, desirable for those who want to get up-to-speed quickly *Important coverage of "under the hood" details that developers will find useful when creating and using a socket or a higher level TCP class that utilizes sockets *Includes end-of-chapter exercises to facilitate learning, as well as sample code available for download at the books companion web site *Tutorial-based instruction in key sockets programming techniques complemented by numerous code examples throughout *Discussion moves quickly into the C Sockets API definition and code examples, desirable for those who want to get up-to-speed quickly *Important coverage of "under the hood" details that developers will find useful when creating and using a socket or a higher level TCP class that utilizes sockets *Includes end-of-chapter exercises to facilitate learning, as well as sample code available for download at the book's companion web site